STRATEGI PENINGKATAN PENGUNJUNG PERPUSTAKAAN STKIP PARIS BARANTAI KOTABARU - Rudy Suryana (STKIP Paris Barantai, 2022)
This study aims to find out how the strategy to increase of visitors to the Library at the STKIP Paris Barantai is carried out by the manager. The indicator of the success of the library is not only seen from the collections and facilities and infrastructure that have met the National Library Standards, but the main thing is how many visitors to the library, for that we need a strategy to increase library visitors. This type of the research is descriptive qualitative where the primary sources are obtained through interviews with the head of the library. Meanwhile, secondary sources were obtained from documents belonging to the STKIP Paris Barantai Kotabaru library and other sources. Data obtained through the interviews, observation and documentation. The technique of presenting data is done by using a table that is described in a narrative manner. The strategy on the information function is carried out by facilitating the search for the required literature by classifying books and placing books on shelves according to their classification. Strategy on the research function by completing the collection. Strategy on the recreational function by providing recreational collections and making the library a comfortable place Keywords: strategy, increasing visitors.